Systematic reviews on platelet transfusions: Is there unnecessary duplication of effort? A scoping review. Issue 1 (1st December 2022) - Avau, Bert; O, Dorien; Veys, Koen; Georgsen, Jørgen; Nahirniak, Susan; Shehata, Nadine; Stanworth, Simon J.; Van Remoortel, Hans; De Buck, Emmy; Compernolle, Veerle; Vandekerckhove, Philippe
Abstract: Background and Objectives: Platelet transfusions are used across multiple patient populations to prevent and correct bleeding. This scoping review aimed to map the currently available systematic reviews (SRs) and evidence‐based guidelines in the field of platelet transfusion. Materials and Methods: A systematic literature search was conducted in seven databases for SRs on effectiveness (including dose and timing, transfusion trigger and ratio to other blood products), production modalities and decision support related to platelet transfusion. The following data were charted: methodological features of the SR, population, concept and context features, outcomes reported, study design and number of studies included. Results were synthesized in interactive evidence maps. Results: We identified 110 SRs. The majority focused on clinical effectiveness, including prophylactic or therapeutic transfusions compared to no platelet transfusion (34 SRs), prophylactic compared to therapeutic‐only transfusion (8 SRs), dose, timing (11 SRs) and threshold for platelet transfusion (15 SRs) and the ratio of platelet transfusion to other blood products in massive transfusion (14 SRs). Furthermore, we included 34 SRs on decision support, of which 26 evaluated viscoelastic testing. Finally, we identified 22 SRs on platelet production modalities, including derivation (4 SRs), pathogen inactivation (6 SRs), leucodepletion (4 SRs) and ABO/human leucocyte antigen matching (5 SRs). The SRs were mapped according to concept and clinical context. Conclusion: An interactive evidence map of SRs and evidence‐based guidelines in the field of platelet transfusion has been developed and identified multiple reviews. This work serves as a tool for researchers looking for evidence gaps, thereby both supporting research and avoiding unnecessary duplication.